Creating spaces for dialogue: a cluster-randomized evaluation of CARE's Community Score Card on health governance outcomes - Sara Gullo; Anne Sebert Kuhlmann; Christine Galavotti; Thumbiko Msiska; C. Nathan Marti; Philip Hastings (BMC, 2018)
Abstract Background Social accountability interventions such as CARE's Community Score Card© show promise for improving sexual, reproductive, and maternal health outcomes. A key component of the intervention is creation of spaces where community members, healthcare workers, and district officials can safely interact and collaborate to improve health-related outcomes. Here, we evaluate the intervention's effect on governance constructs such as power sharing and equity that are central to our theory of change. Methods We randomly assigned ten matched pairs of communities to intervention and control arms, administering endline surveys to women in each arm who had given birth in the last 12 months. Forty-six governance items were reduced by factor analysis into eight underlying scales. We evaluated the intervention's impact on these constructs using local average treatment effect estimates. Results Among intervention-area women who reported a community meeting, we further evaluated the influence of the governance constructs on health-related outcomes: home visit from a community health worker, modern family planning, and satisfaction with health services. A significantly greater proportion of intervention-area women compared to control reported the existence of community groups that provide and facilitate negotiated space between community members and healthcare workers (p = .003). Several governance constructs were positively associated with the health-related outcomes. Further, active participation in the intervention was also positively associated with several governance constructs. Conclusions CARE's Community Score Card© facilitated the creation and claiming of effective and inclusive negotiated spaces in which community members and healthcare workers could vocalize service delivery issues and prioritize actions for improvement. We argue that reliable measurement of governance concepts such as power sharing, equity and quality of negotiated space, collective efficacy, and mutual responsibility will enhance our ability to evaluate social accountability interventions and understand the processes by which they affect change.